2012
DOI: 10.1123/jab.28.3.349
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Algorithms for Body-Worn Sensor-Based Spatiotemporal Gait Parameters to the GAITRite Electronic Walkway

Abstract: This study compares the performance of algorithms for body-worn sensors used with a spatiotemporal gait analysis platform to the GAITRite electronic walkway. The mean error in detection time (true error) for heel strike and toe-off was 33.9 ± 10.4 ms and 3.8 ± 28.7 ms, respectively. The ICC for temporal parameters step, stride, swing and stance time was found to be greater than 0.84, indicating good agreement. Similarly, for spatial gait parameters—stride length and velocity—the ICC was found to be greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
6
34
3
Order By: Relevance
“…Furthermore, we measured spatiotemporal parameters at a rather homogenous speed in our sample and speed might have an impact on accuracy. 10 Spatiotemporal parameters were registered only over a short distance in a controlled setting, and we only included healthy subjects. Reliability and validity (specific parameters) results suggest that the BTS G-WALK ® sensor system might be used in community and athletic settings or clinical studies evaluating treatment effects; however, research in these specific populations is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we measured spatiotemporal parameters at a rather homogenous speed in our sample and speed might have an impact on accuracy. 10 Spatiotemporal parameters were registered only over a short distance in a controlled setting, and we only included healthy subjects. Reliability and validity (specific parameters) results suggest that the BTS G-WALK ® sensor system might be used in community and athletic settings or clinical studies evaluating treatment effects; however, research in these specific populations is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of a 3D gait analysis is that provides extensive data that includes kinematics and kinetics, which often gait assessment tools that record spatio-temporal parameters alone, do not provide. There are commercially available gait assessment tools that can record spatio-temporal gait parameters such as instrumented mats with pressure sensors [10] and body worn sensors that incorporate accelerometers [11]. The limitations of these systems include difficulties in set-up within a clinical environment, where space is often limited, and although they may not be as expensive as the 3D gait analysis system, they are still costly for individual departments or independent rehabilitation clinics to utilize in providing a cost effective clinical assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Good gait speed agreement has also been shown between a Multi-Kinect v2 Instrumented 10-Meter Walkway and motion capture [19] (0.011 m/s for comfortable walking speed and 0.006 m/s for fast walking speed), between a GAITRite mat and body-worn sensors [20] (0.024 m/s for slow, -0.050 m/s for normal, and -0.302 m/s for fast walking speeds), and between Microsoft Xbox One Kinect and motion capture [21] (0.010 m/s for comfortable walking speed, and 0.000 m/s for fast walking speed). The 95% LOA, for all studies that reported them, were relatively narrow and comparable to what was observed here.…”
Section: Walk Testmentioning
confidence: 75%